Seed Bag (ScholarWorks@UARK, 2021)
This seed bag was excavated in 1932 at the Edens Bluff Shelter in Benton County, Arkansas. University of Arkansas Museum Collections. Photo by David Dye, image courtesy of the Arkansas Archeological Survey. Woven bag full of seeds from a domesticated but now extinct starchy-oily seed plant called Chenopodium berlandieri subsup jonesianum (goosefoot), and smaller amounts of an unidentified Asteracae. Please find a blog post sharing more details: https://archeology.uark.edu/artifacts/edensbluffseedbag/ https://scholarworks.uark.edu/uamuhimu/1026/thumbnail.jpg